The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1074/jbc.274.44.31524
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Modulates Gene Expression in Cells of the Marine SpongeSuberites domuncula and Reduces the Degree of Apoptosis

Abstract: Sponges (phylum Porifera) live in an aqueous milieu that contains dissolved organic carbon. This is degraded photochemically by ultraviolet radiation to alkenes, particularly to ethylene. This study demonstrates that sponge cells (here the demosponge Suberites domuncula has been used), which have assembled to primmorphs, react to 5 M ethylene with a significant up-regulation of intracellular Ca 2؉ concentration and with a reduction of starvation-induced apoptosis. In primmorphs from S. domuncula the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
(43 reference statements)
1
35
0
Order By: Relevance
“…Ferguson (1982) measured uptake of amino acids by Cliona celata. Recently, Krasko et al (2000) demonstrated that primmorph cultures of Suberites domuncula were able to take up ethylene from seawater. The uptake of ethylene stimulated cell division, which indicates that it is used by the cells as a substrate.…”
Section: Growth Experimentsmentioning
confidence: 99%
“…Ferguson (1982) measured uptake of amino acids by Cliona celata. Recently, Krasko et al (2000) demonstrated that primmorph cultures of Suberites domuncula were able to take up ethylene from seawater. The uptake of ethylene stimulated cell division, which indicates that it is used by the cells as a substrate.…”
Section: Growth Experimentsmentioning
confidence: 99%
“…The TUNEL technique was then performed in order to detect DNA damage. The specificity of the assay has previously been verified in S. domuncula (Krasko et al 1999). We selected the concentration of H 2 O 2 that enhanced high DNA damage at 1 h followed by a recovery at 6 and 24 h to study if the decrease in levels of ssDNA damage was due to DNA repair or to apoptosis.…”
Section: Dna Integritymentioning
confidence: 99%
“…41 Considering the limitations of this assay, functional studies have been applied here. Until now the searches for caspases in sponges have been without success.…”
Section: Transfection Of Sponge Bcl-2 Into Human Hek-293 Cells M Wienmentioning
confidence: 99%